Analysis Of The Use Of The Dispute Resolution Clause Through Arbitration (Article 79.3) In The Peunaga Cut Ujong Road Construction Agreement Kab. West Aceh Number 001/Pupr-Abar/2024 - Kurdi, Kurdi; Cut Zulfahnur Syafitri (Dinasti Research, 2024)
The real impact of the existence of changes in Article 88 of Law No. 18 of 1999 with Law No. 2 of 2017 concerning Construction Services can be seen in construction service agreements including the Peunaga Cut Ujong Road Development Agreement, West Aceh District No. 001/PUPR-ABAR/2024 whose agreement clause states that the parties agree to resolve disputes through BANI. From here, problems are formulated, namely: First, what are the provisions regarding the arbitration clause in the Peunaga Cut Ujong Road Development Agreement of West Aceh District Number 001/PUPR-ABAR/2024. Second, Does the provision regarding the arbitration clause in the Peunaga Cut Ujong Road Development Agreement of West Aceh District Number 001/PUPR-ABAR/2024 cause potential problems. This research uses normative legal research with statute approach and also conceptual approach. The result of the discussion is that the inclusion of an arbitration clause in the Peunaga Cut Ujong Road Development Agreement of West Aceh District Number 001/PUPR-ABAR/2024 is in accordance with applicable regulations and offers various practical advantages. There are various problems, namely differences in the interpretation of the arbitration clause, the possibility of biased arbitrators, the imbalance of power between the parties to the dispute, and the limitations of the appeal mechanism.